Therapeutic Potential of Liraglutide for Diabetes–Periodontitis Comorbidity: Killing Two Birds with One Stone - Man Yang; Yunqing Pang; Minyu Pei; Yuanyuan Li; Xuemin Yuan; Rongbing Tang; Jing Wang (Journal of Diabetes Research)
Background. The relationship between diabetes and periodontitis is bidirectional, and there is now consensus that periodontitis and diabetes are comorbid. There is a quest for a drug that can be used to treat both conditions simultaneously. This study evaluated the anti-inflammatory and osteoprotective effects of liraglutide (LIRA) on periodontitis in diabetic rats. Methods. Male Wistar rats (n=46) were randomly divided into four groups: control group (n=8), LIRA group (n=8), diabetes-associated periodontitis+0.9% saline group (diabetic periodontitis (DP)+NaCl group, n=15), and diabetes-associated periodontitis+LIRA group (DP+LIRA group, n=15). LIRA treatment lasted for 4 weeks (300 μg/kg/d) after establishment of a rat model of DP. The expression of IL-6, TNF-α, and IL-1β was detected by enzyme-linked immunosorbent assay. The morphological changes of periodontal tissues were observed by hematoxylin–eosin staining. The absorption of alveolar bone and its ultrastructural changes were observed by histomorphometry and microcomputed tomography. The expression of receptor activator of NF-κB ligand (RANKL) and osteoprotegerin (OPG) in alveolar bone was detected by immunohistochemistry. The levels of Runx2 mRNA and ALP mRNA in the gingival epithelium were examined by quantitative real-time polymerase chain reaction. Results. LIRA decreased alveolar bone resorption, improved the microstructure of alveolar bone, and reduced periodontal inflammation and damage (P<0.05). LIRA also reduced blood glucose level and inhibited the secretion of serum IL-6, TNF-α, and IL-1β (P<0.05). In addition, after treatment with LIRA, the ratio of RANKL/OPG was reduced, and the expression levels of ALP mRNA and Runx2 mRNA were upregulated (P<0.05). Conclusions. LIRA not only controls blood glucose level but also reduces inflammation and bone loss and enhances osteogenic differentiation in diabetes-associated periodontitis. Those indicate that LIRA may be used as a potential medicine for the adjunctive therapy of diabetes-periodontitis comorbidity.